2007
DOI: 10.1007/s11071-006-9155-4
|View full text |Cite
|
Sign up to set email alerts
|

A new locking-free shear deformable finite element based on absolute nodal coordinates

Abstract: The absolute nodal coordinate formulation has been recently extended to shear deformable beam or plate elements. This has been accomplished, in practice, by parameterizing the complete volume of the elements instead of a line or surface in the element kinematics description. In the absolute nodal coordinate formulation, the position of any point of the element volume is defined employing independent slope coordinates. The use of a large number of slope coordinates leads to unusual kinematic features that must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Dufva and Shabana [7] eliminated secondorder slope vectors leading to a more efficient reducedorder element for thin plate element. ANCF elements considering transverse shear deformation and related shear locking problem have been studied by Omar and Shabana [8], Sopanen and Mikkola [9], Dufva, Sopanen, and Mikkola [10], Garcia-Vallejo, Mikkola and Escalona [11]. Shear locking can also present in solid elements when applied to thin-walled structures [12], and the reduced integration or higher order elements should be employed for such application.…”
Section: Introductionmentioning
confidence: 99%
“…Dufva and Shabana [7] eliminated secondorder slope vectors leading to a more efficient reducedorder element for thin plate element. ANCF elements considering transverse shear deformation and related shear locking problem have been studied by Omar and Shabana [8], Sopanen and Mikkola [9], Dufva, Sopanen, and Mikkola [10], Garcia-Vallejo, Mikkola and Escalona [11]. Shear locking can also present in solid elements when applied to thin-walled structures [12], and the reduced integration or higher order elements should be employed for such application.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of curvature locking in shear deformable ANCF elements has previously been discussed in the context of beam elements [26]. Here it was concluded that two noded shear deformable ANCF beam elements will suffer from curvature locking when they have non-parallel transverse slope vectors, as shown in Fig.…”
Section: Assessment Of Curvature Thickness Lockingmentioning
confidence: 73%
“…Here several different combinations of generalized coordinates and stiffness descriptions have been investigated. These extensive studies have led to reports and treatment of severe problems with different locking mechanisms [26]. Because of the intensive work of enhancing the ANCF beam el-3.…”
Section: Absolute Nodal Coordinate Formulationmentioning
confidence: 99%
See 2 more Smart Citations